Sulfur Removal from Coal with The Basic Extraction Liquid of Oak Ash - Akçay, Gizem Hazan; Ipek, Ubeyde (My University, 2021)
Desulfurized coal produces high amounts of SOX during combustion. Therefore, many negative environmental impacts such as air pollution and acid rain occur. Coal desulfurization research is very important for environmental and socio-economic development. In this study; it was aimed to desulfurization of coal with oak ash extraction liquid. In this way, sulfur compounds that are harmful to the environment were removed with a waste in nature. Sorgun coal was chosen due to its high sulfur content. Extraction liquids were obtained from different weights of oak ash. Total sulfur and pyritic sulfur values were measured after desulfurization process. In addition, KOH + oak ash liquid mixtures were used for desulfurization to determine the effect of chemicals. For Sorgun coal, the highest total sulfur and pyritic sulfur removal with oak ash were obtained as 28.7% and 57.7%, respectively. Furthermore, the highest pyritic sulfur removal with oak ash + KOH mixtures was obtained as 61.9%. As a result of the study, it was observed that the oak ash extraction liquid was effective to remove total sulfur and pyritic sulfur from coal. It is clear that this study will light on further studies for desulfurization.
Keywords: Coal; Desulfurization; Sulfur; Oak ash